A facile route for growth of CNTs on Si@hard carbon for conductive agent incorporating anodes for lithium-ion batteries. Issue 26 (16th June 2015) - Kim, Chanhoon; Choi, Sinho; Yoo, Seungmin; Kwon, Dohyoung; Ko, Seunghee; Kim, Ju-Myung; Lee, Sang-Young; Kim, Il-Doo; Park, Soojin
Abstract : Conductive agent incorporating Si@HC@CNT anodes were synthesized and exhibited remarkable improvement in long-term cycle performance and rate capability with a high mass-loading of 3.5 mg cm −2 . Abstract : Conductive agent incorporating Si anodes consisting of directly grown carbon nanotubes on hard carbon encapsulating Si nanoparticles were prepared by a one-pot chemical vapour deposition process. Owing to this fabulous structure, Si-based anodes exhibit excellent cycle retention and rate capability with a high-mass-loading of 3.5 mg cm −2 .